2016
DOI: 10.1590/0103-8478cr20150712
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce and marigold intercropping: crops productivity and marigold's flavonoid content

Abstract: Intercropping of vegetables and medicinal plants might produce favorable interactions for both crops, resulting in increased production and profit per unit area. It is known that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Mainly kaempferol glycosides and hydroxycinnamic acid derivatives of B. carinata and S. scabrum were decreased by intercropping and irrigation system. The total flavonoids of marigold and faba bean were not affected by intercropping with lettuce and maize, respectively ( Li et al, 2012 ; Fonseca et al, 2016 ). However, there is evidence that the response is structure-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly kaempferol glycosides and hydroxycinnamic acid derivatives of B. carinata and S. scabrum were decreased by intercropping and irrigation system. The total flavonoids of marigold and faba bean were not affected by intercropping with lettuce and maize, respectively ( Li et al, 2012 ; Fonseca et al, 2016 ). However, there is evidence that the response is structure-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Brandão et al (2014) found good yields of biomass in the intercropping of yarrow, lettuce, and lemon balm. Vieira et al (2012) reported the viability of intercropping lettuce and basil, and Fonseca et al (2016) found increasing the yield of the medicinal species in the intercropping between lettuce and marigold. The spacing showed no effect on height, diameter, and volume of roots when the lemon balm was cultivated in the monocropping system, (Table 2).…”
Section: Agronomic Evaluationmentioning
confidence: 99%
“…The intercropping system is mainly used by small farmers to maximize the utilization of land available for crop production, inputs and labor use in weeding, fertilization, input applications and other cultural treatments. The system also allows increased yield and diversification per unit of cultivated area (CAETANO et al1999;MONTEZANO & PEIL 2006;and FONSECA et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…No cultivo de hortaliças, o consórcio, plantio de duas ou mais culturas na mesma área com diferentes ciclos e arquiteturas vegetativas é uma das práticas agrícolas mais promissoras (Li et al, 2023) que vem sendo usada com sucesso, proporcionando ganho na produção, manutenção da fertilidade do solo (Wang et al, 2014), aumento da eficiência do uso de nutrientes do solo (Barbieri et al, 2019), diversificação de área cultivada (Fonseca et al, 2016), possibilitando colheitas escalonadas e renda adicional ao produtor (Santos e Carvalho, 2013;Gebru, 2015), permitindo ao produtor maior estabilidade na oferta dos alimentos e maior segurança do processo produtivo (Forlani et al, 2022).…”
Section: Introductionunclassified
“…Azedinha (Rumex acetosa L.) é uma olerícola das PANC, também conhecida como azedeira, azedinha-da-horta, azeda-brava e azeda-comum (Pedrosa et al, 2012;Kinupp e Lorenzi, 2014). É rica em compostos antioxidantes, como vitamina C e flavonoides (Viana et al, 2015), devido ao sabor característico, vem agradando os consumidores e mostrando-se promissora no mercado (Lima et al, 2020), sendo consumida como saladas, refogados e em diferentes pratos na gastronomia gourmet (Fonseca et al, 2016).…”
Section: Introductionunclassified